Cancer Immunotherapy with Chimeric Antigen Receptor (CAR) T Cells. Issue 3 (November 2017) - Littman, Dalia; Hexner, Elizabeth
Chimeric antigen receptor T cell (CAR T) therapy recently won its first U.S. Food and Drug Administration approval for use in the treatment of patients aged 3-25 with relapsed or refractory acute lymphoblastic leukemia. CAR T cell therapy is the first approved gene therapy in the USA, and brings with it a new paradigm in cancer therapeutics. Advances in design and manufacturing of CAR T cells have led to dramatic improvements in outcomes for patients with B cell malignancies. As clinical trial experience with CAR T cells grows, adverse events associated with CAR T cell therapy are becoming better understood. Increasing amounts of data suggest that CAR T cell therapy can lead to both dramatic clinical responses and to life-threatening cytokine release syndrome. As more patients are treated with CAR T cells, specialists from a multitude of fields will be involved in monitoring for and/or managing toxicity. Major obstacles in the field include expanding the promise of CAR T cells into other more challenging tumor types, such as myeloid malignancies and solid tumors. In addition to uses in oncology, this review will look to other potential applications of this technology to nonmalignant disease.